Macroeconomic Impacts on Profit Growth in Indonesian Islamic Banking - Muryani Arsal; Sri Nurpiana Arta; Aulia Nurazizah Putri Syarif; Detri Heri Gemita (IECON: International Economics and Business Conference, 2024)
This study investigates the effect of inflation, exchange rates, and GDP on the profit growth of Indonesian Islamic banking firms. Islamic banks operate under a profit-sharing model, differentiating them from conventional banks, which are more susceptible to interest-based fluctuations. Using quantitative analysis, this study collected secondary data from the Indonesia Stock Exchange and Bank Indonesia to assess profit growth and macroeconomic variables. Regression analysis and diagnostic tests were performed to evaluate the relationship between these macroeconomic factors and profit growth. The results reveal that inflation, exchange rates, and GDP  do not significantly affect profit growth in Indonesian Islamic banks. This outcome suggests that Islamic banks may exhibit a natural resilience against common economic pressures due to their unique profit-sharing structure. Unlike conventional banks, Islamic banks appear less influenced by fluctuations in inflation or currency values, providing a potential advantage in emerging markets characterized by economic volatility. The findings imply that Islamic banks offer stability for investors and policymakers during periods of macroeconomic uncertainty. This study contributes to the literature on Islamic banking by offering empirical insights into how macroeconomic factors interact differently with profit growth in this sector. Future research could extend this analysis to conventional banks for comparative insights or explore additional variables affecting Islamic banks' performance over longer time horizons.